DIGITAL MARKETING TO INCREASE SALES OF PADAS STONE HANDICRAFTS IN SILAKARANG BALI - I Gde Wedana Arjawa, Putu Ayu Sita Laksmi, Dewa Ayu Kristiantari (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
This study aims to evaluate the impact of digital marketing on increasing sales of stone crafts in Silakarang, Bali, using quantitative methods. This study involved a sample of 32 respondents from among customers who were familiar with the stone handicraft product. The data collection method involves online surveys and statistical analysis to identify correlations between the digital marketing strategies implemented and the increase in sales. The results of this study are expected to provide a deeper understanding of the effectiveness of digital marketing in the context of the stone craft industry in Silakarang, Bali. The findings from this study can lay the groundwork for local businesses to optimize their digital marketing strategies to increase product visibility and, overall, increase sales in increasingly digitally connected markets.